RETURNING THE GAZE: CULTURE AND THE POLITICS OF SURVEILLANCE IN IRELAND - Thompson, Spurgeon (International Journal of English Studies, 2002)
This essay seeks to examine the modalities of colonial state surveillance as well as severa1 ways in which they have been problematised in recent lrish literary writing, film, painting, photography and practice. Works by Ciaran Carson, Willie Doherty, Dave Fox, Teny George and Jim Sheridan, and Dermot Seymour are al1 therefore examined with the thernatic of "returning the gaze" in rnind. Further, this essay seeks to advance contemporary theories of surveillance away from an information-based or textual model to one which considers the spatial violence of surveillance and the subject positions it delimits, particularly in the context of colonialism and postcolonial theory.